OWE-22 Role of low grade dysplasia small polyps during screening colonoscopies surveillance: A prospective cohort study. (June 2019) - Caroli, Diego; Rosa-Rizzotto, Erik; Saia, Mario; Guido, Ennio; Zorzi, Manuel; Lazzeri, Franca De
Abstract : Background: The role diminutive polyps and small polyps play in the development of advanced neoplasia (AN) or cancer during follow-up (FU) continues to be debated. Recent studies have shown that the risk of AN development during FU is higher in patients with > 5 small polyps but similar in patients with – or – small polyps 2, 3 . Given these findings, the current study aimed to evaluate if current European FU guidelines 1 at first screening colonoscopy according to the number of low-grade dysplasia tubular adenoma < 1 cm ("micropolyps", MP) are too strict. Methods: A longitudinal cohort study was carried out on a representative sample (50%) of patients who underwent a screening colonoscopy (clean colon) in 2010 showing at least 1 polyp. Patients with AN or cancers were excluded. Polyps > 1 cm or villous or high grade dysplasia/carcinoma in situ were considered AN. These patients made a FU colonscopy according to UE screening CCR guidelines. Patients were split up according to European guidelines in Low risk (– MP), Intermediate risk (– MP) and High risk (>5 MP). Data were analyzed by SPSS program. Results: Of 640 patients included in the sample 172 (27%) were included in the surveillance program (mean age 62, 2± 5, 7 yr, 5–0), 120 male (69, 8%). During first colonoscopy (2010) 370 MP were detected (M±SD 2, 1±1, 5, range –3 polyps for each patient). During FU (median 5.5 years), 315 colonoscopies were performed (mean 1.8; range –) and an AN was detected in 23 patients (13.4%): 20/23 tubulovillous microadenoma, 1/23 high grade dysplasia, 2/23 tubular adenoma > 1 cm. The detection of AN among patients in treatment with ASA was non significantly lower than the others. AN detection was lower among Low risk patients (13/108; 10.7%) as compared to Intermediate risk (7/33; 17.5%) and High risk (3/8; 27.3%) (P=ns). According to Kaplan-Meier analysis, the cumulative risk of AN among High risk was significantly increased (p=0.035) (figure 1). No interval cancers were found during the follow-up. Conclusions: These findings suggest that EU guidelines for surveillance colonoscopies for > 3 small LGD polyps are excessively strict. We propose extending the time for a repeat colonscopy FU for these patients to 5 yrs References: Segnan N. et al. European Guidelines for Quality Assurance in Colorectal Cancer Screening and Diagnosis First Edition 2011 Chang MM, et al. Digest Liv Dis 2018; 50: 847–852 Jung YK, et al. Am J Gastroenterol 2018: 113(12):185–1.